Identification and Evaluation of Neuropsychological Tools Used in the Assessment of Alcohol-Related Cognitive Impairment: A Systematic Review - Heirene, Robert; John, Bev; Roderique-Davies, Gareth (Frontiers in Psychology, 2018)
Background: Neuropsychological assessment is central to identifying and determining the extent of Alcohol-Related Cognitive Impairment (ARCI). The present systematic review aimed to synthesize and discuss the evidence appraising the neuropsychological tests used to assess ARCI in order to support clinicians and researchers in selecting appropriate tests for use with this population. Methods: We searched for studies investigating the psychometric, diagnostic and practical values of tools used in the screening, diagnosis, and assessment of Korsakoff’s Syndrome (KS), Alcohol-Related Dementia (ARD), and those with a specific diagnosis of Alcohol-Related Brain Damage (ARBD). The following databases were searched in March 2016 and again in August 2018: MEDLINE, EMBASE, Psych-INFO, ProQuest Psychology, and Science Direct. Study quality was assessed using a checklist designed by the authors to evaluate the specific factors contributing to robust and clearly reported studies in this area. A total of 43 studies were included following the screening of 3646 studies by title and abstract and 360 at full-text. Meta-analysis was not appropriate due to heterogeneity in the tests and ARCI samples investigated in the studies reviewed. Instead, review findings were narratively synthesized and divided according to five domains of assessment: cognitive screening, memory, executive function, intelligence and test batteries, and premorbid ability. Effect sizes (d) were calculated to supplement findings. Results: Overall, several measures demonstrated sensitivity to the cognitive deficits associated with chronic alcoholism and an ability to differentiate between gradations of impairment. However, findings relating to the other psychometric qualities of the tests, including those important for the accurate assessment and monitoring of ARCI (e.g., test-retest reliability), were entirely absent or limited. Additionally, the synthesis of neuropsychological outcomes presented here supports the recent impetus for a move away from discrete diagnoses (e.g., KS, ARD) and the distinctions between them towards more broad and inclusive diagnostic conceptualizations of ARCI, thereby recognizing the heterogeneity in presentation. Conclusions: Based on the evidence reviewed, provisional recommendations for appropriate tests in each domain of assessment are presented, though further validation of most tests is warranted. Review findings can support efficient and evidenced-based test-selection and guide future research in this area.